ANALISIS KEMAMPUAN BERPIKIR KRITIS DALAM PEMECAHAN MASALAH MATEMATIKA - Isnaeni Fatmawati; Prasetyo Budi Darmono; Riawan Yudi Purwoko (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
Critical thinking ability is essential for the future of students, bearing in mind that it used to prepare students for the many challenges that will arise in their lives, careers, and at the level of their obligations and responsibilities. Critical thinking ability is crucial for students to master so that students are more skilled in preparing an argument, checking the credibility of a source, or making a decision. Critical thinking ability is an essential component that students must-have, especially in the process of learning mathematics. That student can create or formulate, identify, interpret, and plan problem-solving. Critical thinking is a high-level ability to think in terms of analyzing, managing strategies, evaluating, building a logical and clear argument, and drawing conclusions in solving a problem. This research is qualitative research with a phenomenological approach. The purpose of this study is to describe the students' critical thinking skills in solving mathematical problems in the material of the Two-Variable Linear Equation System (SPLDV). The subjects of this study were students of class VIII (eight) who had high mathematical abilities at one of the public Junior High Schools in Purworejo. Based on the results of research and discussion, students' critical thinking ability in solving mathematics problems of junior high school students who have top mathematical skills have been able to achieve all the indicators of critical thinking.